Canadian Heart Rhythm Society and Canadian Association of Radiologists Consensus Statement on Magnetic Resonance Imaging with Cardiac Implantable Electronic Devices. Issue 4 (November 2014) - Verma, Atul; Ha, Andrew C.T.; Dennie, Carole; Essebag, Vidal; Exner, Derek V.; Khan, Naeem; Lane, Chris; Leipsic, Jonathan; Philippon, Francois; Sampaio, Marcos; Schieda, Nicola; Seifer, Colette; et al.
Magnetic resonance imaging (MRI) has historically been considered contraindicated for individuals with cardiac implantable electronic devices (CIEDs) such as pacemakers and implantable defibrillators. Magnetic resonance scanners produce magnetic fields that can interact negatively with the metallic components of CIEDs. However, as CIED technology has advanced, newer MRI conditional devices have been developed that are now in clinical use and these systems have had demonstrated safety in the MRI environment. Despite the supportive data of such CIED systems, physicians remain reluctant to perform MRI scanning of conditional devices. This joint statement by the Canadian Heart Rhythm Society and the Canadian Association of Radiologists describes a collaborative process by which CIED specialists and clinics can work with radiology departments and specialists to safely perform MRI in patients with MRI conditional CIED systems. The steps required for patient and scanning preparation and the roles and responsibilities of the CIED and radiology departments are outlined. We also briefly outline the risks and a process by which patients with nonconditional CIEDs might also receive MRI in highly specialized centres. This document supports MRI in patients with MRI conditional CIEDs and offers recommendations on how this can be implemented safely and effectively.